Why a European Agricultural Insurance Scheme is Not a Good Solution. (December 2014) - Azcárate, Tomás García
Summary Would a European agricultural insurance scheme make sense today? My answer is not really. Even if we believe that weather‐related incidents will be even more likely as a consequence of climate change, representing a significant European challenge, in my view a decentralised approach to insurance is more suited to European agricultural diversities. In addition, an EU scheme would be expensive, financed through the budget discipline, resulting in a significant cut in direct payments. I present a first estimation of potential underlying costs that imply significant budget transfers from some west, north and central European Member States to Member States in south and east Europe. The difficulties, therefore, of finding enough political support for the proposal are obvious. This does not mean that nothing can be done. Already harvest insurance is eligible for EU support in the fruit, vegetable and wine sectors and state aids may also contribute to addressing adverse events. The CAP post‐2014 has introduced a risk management toolkit as a new measure in the Rural Development regulation but we should not be too optimistic about the prominence it will assume in national programming.